Upper training cycle for the interpretation of the language of spanish languages: sociodemographic analysis of its graduates 1998-2012 - Inmaculada Sánchez Casado; José Miguel Benítez Merino (INFAD, 2014)
In this paper aims to study the figure of ILSE (Interpreter Spanish Sign Language) not only as a potential resource that promotes inclusion of students with hearing disabilities in the school setting (Sánchez Casado Merino Benítez, 2009) but trying to reflect on their socio-labor situation today, after more than a decade of implementation in Spain as Higher Level Training Programme for Vocational Training, with a duration of 2000 hours, inside the professional family of “Socio-cultural Services and the Community”. This will make a brief historical foundation of her nature, an analysis of the competence profile and sociodemographic initial comparison of enrolled students from the first class nationally, 1998 to 2012, where the evolution of those 12 will be checked promotions analyzed as the total number of graduates of the training cycle and promotion, sex, level of previous studies and the age of completion of Higher Training Programme in order to assess their potential employability in today’s job market. These first results will make an initial proposal to improve the recruitment of new students who choose a superior and professional training on “Interpretation LSE“ according to the actual demand that occurred during these academic courses in Extremadura.